Xi Jinping's Important Discourse on Modern Logistics Construction: Practical Research in Anhui Province - Zuo, Yonggang; Rui, Fei (International Journal of Global Economics and Management, 2024)
Looking back at General Secretary Xi Jinping's roots in northern Shaanxi, cultivation in Zhengding, implementation of policies in Fujian, governance of Zhejiang, and leadership of a major country, logistics and transportation are undoubtedly the areas that General Secretary Xi Jinping has consistently focused on in the long term. Since the 18th National Congress of the Communist Party of China, the development of modern logistics has entered a new stage. General Secretary Xi Jinping has conducted multiple in-depth investigations and research on the logistics market and enterprises, creatively applying Marxist theory on the relationship between production, circulation, and consumption, and pointing out the direction of innovative development of modern logistics in the new stage from the perspectives of industrial chain, supply chain, and value chain. General Secretary Xi Jinping's important discourse on modern logistics construction and its formation and development are of great significance for modern logistics construction. These discourses are the theoretical guidelines for Anhui Province to carry out modern logistics construction in the new era.